Genetic diversity of some Southeast Asian animals: of buffaloes and goats and fishes too - Tan, Soon Guan (Universiti Pertanian Malaysia, 1996)
The genetic relationship between any two populations is a function of differences between them in allele frequencies, with this relationship usually expressed in tenns of a genetic distance. Thus, if two populations are homozygous for different alleles at a particular locus, the distance is the maximum possible while if the allele frequencies in the two populations are identical, the distance is zero. The estimated genetic distances may vary among loci and the most accurate measures of relationships will be obtained by averaging over many loci (Nei, 1978). In animal breeding, it is expected that a cross between two animals originating from two populations with a large genetic distance between them will result in maximum heterosis or hybrid vigour. Although many estimates of genetic distances are available, Nei's standard genetic distance, D, (Nei, 1972) had been extensively used in studies of livestock populations and breeds. The genetic relationships among livestock populations can also be represented graphically by means of a dendrogram based on the genetic distances and clustered by methods such as the neighbour joining method of Saitou and Nei ( 1987) or the unweighted pair group method with arithematic averaging (UPGMA) of Sneath and Sokal (1973). In order to get good estimates of genetic relationships, Lewontin (1974) suggested that 50 or more loci be studied while Barker (1994) demonstrated the marked effects using a small number of loci can have on estimates of relationships for populations within a species. Since in the past, many studies of genetic relationships among livestock breeds worldwide have not used more than 15 loci (Gonzalez et al., 1987; Tunon et al., 1989; Zanotti Casati et al., 1990) their interpretations need to be taken with caution.